A Novel Immunoassay for Malondialdehyde-Conjugated Low-Density Lipoprotein Measures Dynamic Changes in the Blood of Patients Undergoing Coronary Artery Bypass Graft Surgery - Samata S. Pandey; Adam Hartley; Mikhail Caga-Anan; Tareq Ammari; Ameer Hamid Ahmed Khan; Bao Anh Vu Nguyen; Chiari Kojima; Jon Anderson; Steven Lynham; Michael Johns; Dorian O. Haskard; Ramzi Y. Khamis (MDPI AG, 2021)
Oxidized low-density lipoproteins play an important role in tissue pathology. In this study, we report a sensitive novel enzyme-linked immunosorbent assay for the detection of malondialdehyde-modified low-density lipoprotein (MDA-LDL), a key component of oxidized LDL. The assay is capable of measuring a variable presence of MDA-LDL within human plasma and serum. We demonstrate the robust nature of the assay on samples stored for over 20 months, as well as high inter-operator reproducibility (r = 0.74, p < 0.0001). The assay was capable of detecting dynamic changes in patient blood samples after coronary artery bypass graft surgery, indicating synthesis or release of MDA-LDL with the oxidative stress of surgery, followed by homeostatic clearance. This robust, sensitive and specific assay for circulating MDA-LDL will serve as a valuable translational tool for the improved detection of oxidative forms of LDL in response to a range of physiological or pathological stimuli, with potential clinical applicability.